2017
DOI: 10.1002/ece3.2917
|View full text |Cite
|
Sign up to set email alerts
|

A worldwide phylogeography of the whiteworm lichens Thamnolia reveals three lineages with distinct habitats and evolutionary histories

Abstract: Thamnolia is a lichenized fungus with an extremely wide distribution, being encountered in arctic and alpine environments in most continents. In this study, we used molecular markers to investigate the population structure of the fungal symbiont and the associated photosynthetic partner of Thamnolia. By analyzing molecular, morphological, and chemical variation among 253 specimens covering the species distribution range, we revealed the existence of three mycobiont lineages. One lineage (Lineage A) is confined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 56 publications
3
33
0
Order By: Relevance
“…The three Pseudephebe species show no substantial differentiation with regard to photobiont use, based on haplotype distribution, Fst values and the specialization parameter d' for both ITS and RPL10A. This scenario aligns with previous reports of closely related lichenized fungi sharing the photobiont pool partially or completely (Beck et al 1998;Hestmark et al 2016;Onuţ-Brännström et al 2017;Singh et al 2017;Dal Grande et al 2018;Ossowska et al 2019) and opposes to cases in which ecological speciation drove photobiont differentiation, as in the Lichina-Rivularia symbiosis (Ortiz-Álvarez et al 2015). This is reflected in the most prevalent haplotypes 1 (ITS) and 2 (RPL10A) that are shared by the three mycobiont species across continents and regions spanning different climatic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The three Pseudephebe species show no substantial differentiation with regard to photobiont use, based on haplotype distribution, Fst values and the specialization parameter d' for both ITS and RPL10A. This scenario aligns with previous reports of closely related lichenized fungi sharing the photobiont pool partially or completely (Beck et al 1998;Hestmark et al 2016;Onuţ-Brännström et al 2017;Singh et al 2017;Dal Grande et al 2018;Ossowska et al 2019) and opposes to cases in which ecological speciation drove photobiont differentiation, as in the Lichina-Rivularia symbiosis (Ortiz-Álvarez et al 2015). This is reflected in the most prevalent haplotypes 1 (ITS) and 2 (RPL10A) that are shared by the three mycobiont species across continents and regions spanning different climatic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…In certain cases, differential levels of resolution between ITS and more variable markers is being resolved by recognizing infraspecific taxa, such as in the lichenforming ascomycete Thamnolia (Onuţ-Brännström et al 2017;Ioana et al 2018;Jørgensen 2019); in other cases, e.g. the various IGS-defined clades of the ubiquitous basidiomycete Schizophyllum commune (James et al 2001), no formal taxonomy has been implemented.…”
Section: Lack Of Resolution Of the Its And Use Of Secondary Barcodesmentioning
confidence: 99%
“…In our recent study, which was based on the analyses of six nuclear markers (genes or noncoding regions) of a worldwide sample of Thamnolia (including the Nelsen & Gargas (2009) dataset), we showed the existence of three well-supported lineages with different chemistries and geographical distributions (Fig. 1) (Onut-Brännström et al 2017). One lineage (‘Lineage C’, ibid .)…”
Section: Introductionmentioning
confidence: 93%
“…They mainly occur in alpine and arctic environments where extensive colonies are often formed. Even if signs of past or infrequent recombination have been found (Onut-Brännström et al 2017), Thamnolia has never been found fruiting and it is believed to disperse exclusively by thallus fragments (Andrei et al 2006–2007) or mitospores formed in pycnidia (Lord et al . 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation